Improvement in mechanical properties of reinforced thermoplastic elastomer composite with kenaf bast fibre - Anuar, Hazleen; Ahmad, Zuraida (Elsevier, 2011)
This paper report on the development of thermoplastic elastomer composite reinforced with 20 vol.% kenaf fibre. Two types of impact modifier were blended with polypropylene (PP) namely; thermoplastic natural rubber (TPNR) and polypropylene/ethylene–propylene–diene–monomer (PP/EPDM). Both composites were produced via double melt blending method using Haake internal mixer before they were compression moulded. The ratio of thermoplastic:elastomer was 70:30 for both polymer blends. Due to incompatibility between matrix and reinforcement, maleic anhydride polypropylene (MAPP) was added as in the case of treated composite. It was found that the tensile strength for TPNR is about 12% higher than the PP/EPDM matrix. The present of kenaf fibre (KF) and MAPP however has significantly increased the tensile strength of the PP/EPDM composite by approximately 81% while only 55% increment attained in TPNR–KF–MAPP as compared to unreinforced TPNR. Apart from that, flexural properties and impact strength are greatly improved for treated kenaf fibre composite. This shows that KF has imparted its tensile strength to the PP/EPDM system with good interaction provided by the compatibilizer agent. Scanning electron micrographs (SEMs) revealed that the improvement achieved in mechanical properties was due to the interaction between both matrix systems and kenaf fibre.